METHODOLOGY FOR DETERMINING THE THRESHOLD ZONES OF ENERGY SUPPLY BY THE DYNAMICS OF HEART RATE AND LACTATE IN RUNNING STEP TESTS TO FAILURE - Zagurskiy N.S. ,; Mikhalev V.I. ,; Romanova Ya.S. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to improve the efficiency of biathletes' training process management based on the assessment of aerobic (AMT) and anaerobic metabolism (AnMT) thresholds in running step tests to failure. Methods and structure of the study. In scientific work, the Conconi test was used, which was performed on a 400-meter athletics track. Athletes carried out continuous running with a gradual increase in speed every 200 m, starting from running at a heart rate of 120-130 beats/min. During the test, the values of heart rate and running speed were continuously recorded. The increase in running speed and heart rate was monitored using Polar vantage NV sports testers. The results were processed using a special computer program Polar Electro Oy. The study involved nine biathletes (Candidate Master of Sports in biathlon). The average age of the subjects is 20 years. The study took place at the SibSUPhE stadium. Results and conclusions. The average values of heart rate and running speed showed a high correlation at the threshold zones of energy supply. The mean PAO values were 157.2 and 156.9 beats/min in both tests, the correlation coefficient was 0.75. Mean AnMT values were 177.2 and 173.6 beats/min in the Conconi test and lactate test, respectively, with a correlation coefficient of 0.72. The average values of the maximum heart rate were 193.4 and 192.1 beats/min in both tests, the correlation coefficient was 0.93. Based on the results obtained, it is recommended to regularly perform special load tests to monitor the level of performance of biathletes. Testing data testify to the high information content of the indicators of AMT and AnMT for the purposes of managing the training process and calculating individual intensity zones.